Pragmatics of poetry: the communicative act of praise in spanish renaissance poetry - Luján Atienza, Ángel Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This paper considers the act of celebration and praise as basic in all kind of poetry. Praise is, in its purest aspect, an uncalled-for movement of language toward a divinity, out of sheer admiration. This communicative act is analyzed in the framework of speech act theory and put into practice in Spanish Renaissance poetry of praise. Eventually, topics attached to this genre of circumstance poetry are focused as logical consecuences of the utterance conditions. Therefore, these topics, codified by Ancient Rhetoric, are considered not as fanciful formulae but as necessary expressions of the act of praising.